Matemática e interdisciplinariedade: um desafio para os professores de duas escolas públicas de Manaus - Paulo, Monique de Oliveira (2013)
This work grew out of an investigation focused on interdisciplinarity, which was prepared with the purpose of making an analysis of teachers' conceptions of mathematics, research subjects, about the interdisciplinary teaching across the curriculum. In this path were also analyzed the practices of these professionals. The survey was conducted in two public schools located in the city of Manaus. To achieve our goal we chose a qualitative research method based on Creswell (2007) and Gil (2010). To guide this process, we adopted epistemological approach to phenomenology, as this enabled us to know the ontological aspects reported by the research participants. Data were obtained through the techniques of observation (in the classroom) and interviews (made with teachers). Participated in the survey, seven teachers, four teachers of the first school and three of the second, both belonging to the same district coordination office. With the results, we found that most teachers have a general idea of interdisciplinarity and we know the requirement of curriculum proposals on interdisciplinary teaching, however, it was not what we found in the practice of most of these teachers. Therefore, the existence of an interdisciplinary approach to support the teaching-learning process remains undoubtedly a challenge. Key-words: Mathematics. Interdisciplinarity. Curriculum. Teachers.